2011
DOI: 10.1590/s2179-10742011000200006
|View full text |Cite
|
Sign up to set email alerts
|

An FET-based microwave active circuit with dual-band negative group delay

Abstract: Recent studies proved that certain electronic active circuits are capable to exhibit simultaneously a negative group delay (NGD) and amplification in microwave frequency bands. One of the simplest topologies generating this counterintuitive NGD function effect is formed by a series RLC-network in cascade with a transistor. By using this cell, similar to the classical electronic functions, dual-band NGD microwave devices with loss compensation possibility can be designed. Theoretic demonstrations concerning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…In this section, we propose a cancellation technique of the resonance effect essentially modelled by parallel LC-network. To do this, the microwave NGD circuit formed by a transistor associated with RLC series network developed in [41][42] is used. Fig.…”
Section: Resonating Effects Cancellation With Ngd Circuit For Modulatmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we propose a cancellation technique of the resonance effect essentially modelled by parallel LC-network. To do this, the microwave NGD circuit formed by a transistor associated with RLC series network developed in [41][42] is used. Fig.…”
Section: Resonating Effects Cancellation With Ngd Circuit For Modulatmentioning
confidence: 99%
“…So, the applications are still limited in low frequencies. To overcome this physical roadblock, more recently, NGD active topologies for microwave signals were proposed [41][42][43][44]. These active topologies are constituted by RF transistor or amplifier associated with passive lumped networks.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental analyses confirm that this innovative physical function allows to generate an output signal with wave fronts propagating in advance of its input under certain conditions [7][8][9][10][11][12][13][14]. Inversely to the ordinary medium, in this case, the time delay can be assumed as negative [4][5][9][10][11][12][13][14][15][16]. It was pointed out [19][20] that this NGD effect does not forbid the causality principle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that certain passive [1][2][3][4][5][6][7][8] and active [9][10][11][12][13][14][15][16][17][18] circuits are susceptible to exhibit the negative group delay (NGD) function at low-and RF-/microwavefrequencies. Theoretical and experimental analyses confirm that this innovative physical function allows to generate an output signal with wave fronts propagating in advance of its input under certain conditions [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation